Pergeseran Paradigma dalam Disabilitas - Meilanny Budiarti Santoso; Nurliana Cipta Apsari (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2017)
Paradigm shift in understanding disabilities need to be delivered in line with the spirit of reformation and democratization lies on strengthening fundamental pillars of human rights. This article is using literature and documentation study. The paradigm in addressing or providing services to people with disabilites have shifted, starting with The Traditional model, which was charity in nature, shifted toward The Individual Model – Medical Model, emphasizing rehabilitation for disabilities population. The second model were felt insufficient to eliminate the obstacles dealt by the disabilities, thus the professionals developed the third paradigm, which is The Social Model, where focus of services are meant to create social change – community change. Currently, services for disabilites population are based on the Inclusion Model, which is inclusive development – inclusive society. The inclusive approach is utilized to present the disabilities population in the lives of the community, thus accomodating more of human rights of the disabilites population.